Implementasi Fermentasi Tempe sebagai Media Pembelajaran Ilmu Pengetahuan Alam - Silvi Hurmaidah; Siti Nursucia Ningsih (Medan Resource Center, 2026)
Fermentation is one of the fundamental biotechnology topics in elementary science education, yet it is often taught theoretically with limited opportunities for hands-on investigation. This study aimed to examine the tempeh fermentation process using Glycine max inoculated with Rhizopus oligosporus and to analyze the role of aeration in supporting fungal growth as a basis for developing contextual science learning activities. The study employed a simple experimental design with a descriptive qualitative approach. Fermentation was observed for 48 hours by documenting changes in soybean texture, mycelial development, aroma, and physical characteristics in perforated plastic containers. The results showed that fine white hyphae emerged within the first 24 hours, indicating the initial growth of Rhizopus oligosporus, while after 48 hours the soybeans had developed into compact tempeh with uniform white mycelial coverage and a characteristic fermented aroma. Adequate aeration provided by the perforated containers supported consistent fungal growth throughout the fermentation process. These findings demonstrate that tempeh fermentation is not only an effective medium for illustrating microbial activity and fermentation concepts but also a contextual, ethnoscience-based learning resource that can enrich elementary science instruction through simple experimental activities.